METHODOLOGICAL BASIS FOR STRATEGIC ASSESSMENT OF RURAL TERRITORIES DEVELOPMENT MANAGEMENT SYSTEM UNDER DECENTRALIZATION IN UKRAINE - Horban , Alina (Theory and Practice of Public Administration, 2020)
In article it is defined methodological basis for strategic assessment of rural territories development management system under decentralization in Ukraine. The elements of this process are revealed: goals, principles, methods, tools, criteria and sequence of actions. It is emphasized that the purpose of strategic assessment of the system of management of rural territories development in the context of decentralization is to obtain reliable information about the activities of public authorities in the context of implementing certain long-term community transformations in order to make timely administrative decisions.The following approaches to the strategic assessment of rural territories development management system are distinguished: systemic (unity of all components of the process), complex (integrity of the elements of assessment), functional (orientation to management functions and their implementation), organizational (diagnostics of organizational structure of institutions).An integrated approach to the implementation of the strategic assessment of rural territories development management system is offered, through analysis of the activities of all structural units and their relationship with other stakeholders regarding compliance with the provisions of the regulatory documents in accordance with the defined management functions by certain criteria. The matrix of the institutional capacity assessment of the rural territories development management system is presented.A method of determining the stages of the life cycle of a rural territories development management system under decentralization is revealed, which will allow to distinguish following states: recently established management system; dynamically growing management system; mature management system; recession or crisis management system.The components of strategic assessment of rural territories development management system under decentralization are revealed: monitoring of processes of budgeting and financial management of territorial community, processes of providing of administrative and social services by key criteria of democratic governance, advocacy, inclusivity and integration, financial security of the community using the benefits of public-reengineering methodology, benchmarking and outsourcing, strategic and content analytics tools.